MADRASAH RAMADAN DALAM DEMENSI HABLU MIN ALLAH WA HABLU MIN AL-NAS - Dr. Muh. Haras Rasyid, M.Ag (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
Madrasah Ramadan which serve as the main variable title of this article, illustrates the religious activities carried out by the Islamic community in the holy month of Ramadan is a portion of the formation and religious education. The purpose of this paper is to increase knowledge and motivation that religious activities are carried out in the holy month of Ramadan, such as prayer, fasting, reading the Koran and issued alms, not only closely keep a good relationship with Allah. but also loaded with values ​​that maintain good neighbor relations. By him, the more do the acts of worship in the holy month of Ramadan, then progressively increased closeness servant to Allah. and creating a positive harmony between human beings in public life